What determines the output drop after an energy price increase: Household or firm energy share? - Rajeev Dhawan; Karsten Jeske (Federal Reserve Bank of Atlanta, 2007)
During the past thirty-five years, energy use as a fraction of output has dropped significantly at both the household and the firm levels. Therefore, we investigate a dynamic stochastic generalized equilibrium model economy's response to an energy price hike for different firm and household energy shares. Simulation results indicate that the economy's output response is mainly determined by the firm energy share. Increasing the household energy share while keeping firm energy share constant actually decreases the output response.
Keywords: E32; Q43; 330; energy prices; business cycles; durable goods; Stromtarif; Energiekonsum; Privater Haushalt; Unternehmen; USA; Stromtarif; Energiekonsum; Privater Haushalt; Unternehmen; USA